Menciptakan Sekolah Berkarakter Guna Meningkatkan Mutu Pendidikan Di Indonesia - Ahmad Rizki Muhibi; Chindi Widya Arifin (Pusat Riset dan Inovasi Nasional, 2023)
A school with character is a school that does not only focus on academic achievement, but also on building positive student character. The strategy for creating a school with character must involve all stakeholders, including students, teachers, parents and school staff. This article shows that there are several strategies that must be implemented by school principals in terms of creating a school with character, the first is to form a character team consisting of teachers, parents, and students to create a positive and supportive school culture, the second is to integrate the values character in the curriculum and learning in the classroom, the third provides good examples in everyday life to inspire students, the fourth provides space and time for students to participate in extracurricular and social activities, and the last provides support and guidance for students in need